Secretory symptoms from metastatic adrenal cortical carcinoma responding to octreotide. Issue 834 (April 1995) - Pandha, H. S.; Harrington, K.; Saini, S.; Lynn, J.; Peters, M.; Waxman, J.
Abstract : The prognosis of patients with metastatic adrenal cortical carcinoma is poor, and their disabling symptoms are usually unresponsive to conventional therapy. A patient with Cushing's syndrome secondary to a secretory adrenal cortical carcinoma was treated with octreotide, endocrine therapy and chemotherapy having failed. Treatment led to a dramatic relief of her symptoms with a fall in corticosteroid secretion. Somatostatin analogue therapy for this tumour should be encouraged in view of the lack of alternative palliative treatment.